A construção da convivência democrática no ensino fundamental - Medeiros, Viviane Cristina (2017)
This dissertation presents a qualitative and exploratory research, of the ethnographic type, on the construction of democratic coexistence in the context of Elementary School, in a public school of the municipal network of Curitiba. The objective was to identify the singularities of the educational practices that participate in the construction of democratic coexistence in the school. The research was developed in the following stages: elaboration of the theoretical reference, accomplishment of field work and analysis. The theoretical reference was drawn from authors such as Apple and Beane (2001), Araújo (2002, 2004), Puig et al. (2000), Fierro Evans and Tapia (2013), Fierro Evans (2008, 2012, 2015), Fierro Evans, Carbajal Padilha and Martinez-Parente (2010), Fierro Evans and Fortoul Ollivier (2015), Mena and Rodríguez (2003), Mena (2008, 2011), Garcia (2014), Jares (2008), Córdoba; Del Rey and Ortega-Ruiz (2014), Carbajal Padilha (2013), among others. For the data collected in the field, semi-structured interviews were applied, as suggested by Bogdan and Biklen (1991). In all, fourteen participants were interviewed, among them: teachers, students, employees, management and pedagogical staff. The criterion for the choice of participants was the involvement with the democratic educational practices carried out in the daily life of that school. Selection followed intentional sampling by intensity, found in Patton (1990). For the interpretative reading of the data, the Content Analysis method was used, from a perspective proposed by Bardin (2011), we elaborated three categories, which allowed us to perceive some singularities in the construction of the coexistence of that school. They are: to legitimize decisions; open dialogue and a sense of collectivity. Among the results, we can highlight that for the interviewees, the singularities present within the democratic educational practices carried out at that school include the involvement of the collective in the actions of the school and that, for this, it is necessary to share needs and also desires that sustain the way those people want to live together.